(untitled) (Scientific journal of the Fergana State University, 2023)
Transparent conductive Sn based electrodes are the most relevant solutions to many problems in physics and electronics. This article discusses the use, production methods, resistance, ratio, manufacture and application of transparent conductive Sn based electrodes